ÇÖZÜM ODAKLI SOSYAL HİZMET MÜDAHALESİNİN ÜNİVERSİTE ÖĞRENCİLERİNİN UMUTSUZLUK VE STRES DÜZEYLERİNE ETKİSİ - THE EFFECT OF SOLUTION FOCUSED SOCIAL WORK INTERVENTION ON COLLEGE STUDENTS’ HOPELESSNESS AND STRESS LEVELS - Melek Zubaroğlu Yanardağ; Emine Özmete (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Objective: This research aims to investigate the effects of “Social Work Intervention Based on Solution Focused Brief Therapy (SFBT) on college students’ hopelessness and stress levels. Method: A total of 24 college students who applied Hacettepe University Beytepe Psychological Counseling Unit in the fall of 2015-2016 academic year were assigned to intervention and control groups. SFBT between 4-8 sessions were conducted with each student from intervention group during the intervention. A quasi-experimental research model based on pretest-posttest with comparison group has been chosen for the study. Mann Whitney U test was utilized to analyze results. Results: For the Hopelessness Scale the difference among scores for the Motivation Loss Subscale was statistically significant (p < 0.05). Similarly, the difference among the total Hopelessness Scale score and the two other Hopelessness Subscale scores (Expectations and Feelings About Future and Hope Subscales) and for Perceived Stress Scale scores were statistically significant in favor of the intervention group (p < 0.001). Effect size of the intervention was found to be large for all the scales and for most of subscales. Conclusion: Results indicate that the social work intervention based on SFBT was statistically significant and effective on the college students.